Cultural preservation through ICT amongst ethnic minorities in Malaysia - Choo, Yeong Khong; Darshan Singh, Sarjit Singh; Abu Samah, Asnarulkhadi; Talib, Ahmad Tarmizi (Human Resource Management Academic Research Society, 2021)
Information and Communication Technology (ICT) has gradually evolved into a necessity for all members of society, whether in urban or rural areas. As ICT has penetrated almost every aspect of human daily lives, its impact on the culture and identity of ethnic minorities has been widely debated in recent years. On the one hand, ICT has been labelled as the catalyst that eroded the culture of the ethnic minorities; on the other hand, it has the potential to play a critical role in preserving the ethnic minorities’ endangered culture. This is worth pondering as many ethnic minorities in Malaysia are facing the threat of losing their cultural identity through various means such as being assimilated into mainstream society, can ICT be a beneficial instrument for cultural preservation to enhance the ethnic minorities’ cultural survival, or is it simply a rhetorical thought? Therefore, this article is significant as it endeavours to discuss the factors for the decline of the ethnic minorities’ cultural identity and aims to broaden perspectives on ICT and ethnic minorities’ cultural research in Malaysia.